Effects of Brief Intervention of Behavioural Change on Pain, Mobility, Function, and Quality of Life in Patients with Chronic Ankylosing Spondylitis: A Randomised Clinical Trial - Raheel Younus, Tazeem Akhtar, Hafiz Syed Ijaz Ahmed Burq, Rabbiya Sarwar, Wadha Kamran, Ahmed Jamal, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Exercise is essential for maintaining the flexibility and functionality of the joints in patients with ankylosing spondylitis. Additionally, it could ease pain, enhance posture, correct muscular imbalances, facilitate breathing, and generally enhance the quality of life. However, since patient education is poorly structured, patients fail to consider this significant element. Objective: To determine the effects of brief intervention of behavioural change on pain, mobility, function, and quality of life in patients with chronic ankylosing spondylitis Methods: This was a randomized controlled trial with 80 patients in two groups: brief intervention and control. Purpose sampling was used to enrol ankylosing spondylitis patients aged 18 to 60 with stable medical management. Patients with respiratory, cardiac, neurological, pregnancy, or inability to walk unassisted were excluded. All participants provided written informed consent. Cardiorespiratory test duration, physical activity duration per week, flexibility measured by chest expansion, back pain usual, back pain at night, global disease activity, Bath Ankylosing Spondylitis Functional Index (BASFI) and Ankylosing Spondylitis Quality of Life (ASQoL) scale. Week 0 before treatment, 6th week end, and 12th week follow-up were assessed. Data was analysed in SPSS 25.0. Results: The results showed that the demographic variables were equally distributed in both groups without a significant association to any group (p value >0.05) except for urban residence where urban residents were having more percentage of ankylosis spondylitis. The results regarding outcome variables post-interventional 8th week showed that Cardiorespiratory test duration 881±(47.23) and 812±(56.89), Flexibility, chest expansion 6.7±(2.75) and 5.2±(2.14), Back pain usual 2.7±(0.79) and 3.4±(1.04), Back pain at night 3.8±(1.78) and 4.4±(1.54), Global disease activity 6.2±(1.97) and 6.7±(2.03), Bath Ankylosing Spondylitis Functional Index (BASFI) 7.4±(1.16) and 7.2±(1.69) and Ankylosing Spondylitis Quality of Life (ASQoL) scale 12.6±(1.25) and 15.7±(1.05). while the p value (<0.05) showed significant difference in favour experimental group, brief intervention for all variables. Similarly, the follow up results measured at 16th week were significantly different in favour experimental group, brief intervention for all variables, p value (<0.05 Conclusion: The findings of study concluded that brief intervention-based health improving physical activity was significantly on pain, mobility, function, and quality of life in patients with chronic ankylosing spondylitis. Keywords: Brief Intervention, Physical Activity, Ankylosing Spondylitis, Back Pain, Spinal Mobility